A new strategy: realization of organic heteroepitaxy and organic alloys based on the similarity of CC and NN. Issue 17 (14th April 2023) - Guan, Shaoqing; Zhao, Guixia; Sun, Yichen; Tang, Zhenxun; Pan, Jiahong; Wang, Jianjun; Ji, Zhuoyu; Wang, Xiangke
Abstract : The similarity of NN and CC in trans -4, 4′-azobis(pyridine) and trans -1, 2-bis(pyridin-4-yl)ethene offers an innovative approach for creating controllable and versatile organic heterostructure and organic alloy. Abstract : Heteroepitaxial growth and alloys with novel physicochemical properties are attracting great attention in the photoelectric field, and inorganic heteroepitaxial growth and inorganic alloys have been well controlled via changing experimental conditions. Meanwhile, organic heterostructures (OHSs) and organic alloys (OAs) are less studied due to strict requirements for lattice parameters. Moreover, the occurrence of organic homogeneous nucleation is another main problem to solve in OHSs and OAs. Herein, by taking advantage of the similarity between NN and CC, we present a cocrystal strategy to maintain the molecular arrangement and lattice parameters, and perfect lattice matching is realized in the case of mutual substitution of NN and CC in molecules. Furthermore, we successfully achieved perfect organic heteroepitaxy and organic alloys with the same materials. We expect the realization of more versatile OHSs and OAs by introducing NN and CC into the photoelectric field.